The Relevance of Publications on the Subject of Innovation in the Portuguese Language over the Last 30 Years: A Bibliometric Contribution - Estevao, Janete Saldanha Bach; Shima, Walter (Qualitative and Quantitative Methods in Libraries, 2017)
This study presents the results of bibliometric research on the subject ‘innovations and (neo) Schumpeterian approaches’. Specifically, the study intends to show the relevance of the publications in Portuguese over the last thirty years. On a different study into the same subject and period of coverage (Fagerberg, Fosaasa, & Sappraserta, 2012), it could be seen, as a result of repeated research, that there were not many publications in English and there was a lack of methodology to indicate better criteria for searching, content analysis, and research patterns when distinct databases were used.